We can solve this system of equations using elimination or substitution method.
Elimination method:
1. Multiply the first equation by 6 and the second equation by 1 to get:
54x + 6y = 180
6x - y = 15
2. Add the two equations together to eliminate y:
60x = 195
3. Solve for x:
x = 3.25
4. Substitute x = 3.25 into one of the original equations to solve for y:
9(3.25) + y = 30
y = 1.75
5. The solution is (x,y) = (3.25,1.75)
Substitution method:
1. Solve one of the equations for one variable in terms of the other:
y = 30 - 9x
2. Substitute this expression for y into the second equation:
6x - (30 - 9x) = 15
3. Simplify and solve for x:
15x = 45
x = 3
4. Substitute x = 3 into one of the original equations to solve for y:
9(3) + y = 30
y = 1.5
5. The solution is (x,y) = (3,1.5)
Both methods give the same solution of (3,1.5) or (3.25,1.75).
9x+y=30 6x-y=15
1 answer